The Pyrenees: death of a border, birth of a hinge? - SANGUIN, André-Louis; GUIRAUD, Frédérique (European Spatial Research and Policy, 1995)
At the end of the 1950s the Pyrenean Mountain Range stili represented a physical barrier with rare entry and exit points. From the Treaty of the Pyrenees (1659) to the Franco dictatorship, this inescapable element was reinforced by the almost mutual indifference of two states tuned back to back. From the 1960s, the touristic rush of citizens from the European Community burst this double lock to progressively secure the Iberian Peninsula to the rest of Europe.